Multiscale MD simulations of wild‐type and sickle hemoglobin aggregation. Issue 11 (18th May 2022) - Olagunju, Maryam O.; Loschwitz, Jennifer; Olubiyi, Olujide O.; Strodel, Birgit
Abstract: Sickle cell disease is a hemoglobinopathy resulting from a point mutation from glutamate to valine at position six of the β ‐globin chains of hemoglobin. This mutation gives rise to pathological aggregation of the sickle hemoglobin and, as a result, impaired oxygen binding, misshapen and short‐lived erythrocytes, and anemia. We aim to understand the structural effects caused by the single Glu6Val mutation leading to protein aggregation. To this end, we perform multiscale molecular dynamics simulations employing atomistic and coarse‐grained models of both wild‐type and sickle hemoglobin. We analyze the dynamics of hemoglobin monomers and dimers, study the aggregation of wild‐type and sickle hemoglobin into decamers, and analyze the protein–protein interactions in the resulting aggregates. We find that the aggregation of sickle hemoglobin is driven by both hydrophobic and electrostatic protein–protein interactions involving the mutation site and surrounding residues, leading to an extended interaction area and thus stable aggregates. The wild‐type protein can also self‐assemble, which, however, results from isolated interprotein salt bridges that do not yield stable aggregates. This knowledge can be exploited for the development of sickle hemoglobin‐aggregation inhibitors.